Evaluating Epidemiology, Symptoms, and Routes of COVID-19 for Dental Care: A Literature Review - Ana Regina Casaroto; Javad Jamali; Fatemeh Amini; Milad Talebzade Toranji; Gözde Kayasöken (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
COVID-19 has now been spread worldwide and has become a significant concern. Despite universal attempts for repressing this disease, it increasingly spreads due to the prevalence pattern of the infection. According to a new report made by the WHO situation report (May 16, 2020), 2019-nCoV has affected more than 454395 reported cases. A few facilities of dental care in influenced nations are closed or are merely giving negligible treatments for some emergency cases. The coronavirus (COVID-19) is found abundantly in nasopharyngeal and salivary secretions of the affected patient. It is also transmitted through respiratory particles and contact with the infected surface; that's why dental jobs and dental professionals are more at risk. Therefore, the present study was an attempt was made to propose epidemiology symptoms and routes of COVID-19 for dental care for patient screening.